Biokomposit Bermatrik Pati Sagu dengan Variasi Fraksi Volume Serat Rami - Raharjo, Rudianto (Rekayasa Mesin, 2014)
This research is applied for food container. Food container must have high bending strength, saving food contact and easy decomposes naturally. This study focus on producing the biocomposite for container application as a polystyrenes substitution. Sago extract, cytosine 40 %, Glycerol 20 % and 70 C of gelatinization temperature were used as materials in this study. The filler used in the process has no many variation, start 10%, 20%, 30%, 40% and 50% from the biocomposite volume fraction by using the bending test by ASTM C393 (1997). The result of this study was the bending strength and the migration of material to the volume fractions of jute fiber. The highest bending strength at 40% volume fraction was 6 MPa and the slowest stress at 2 MPa in 10% volume fraction. This result showed the material used in this study was safe for food container.Keywords: bio-composite, fiber, sago, bending strength.